Monostotic Fibrous Dysplasia of the Lumbar Spine With Secondary Features of Solid Variant Aneurysmal Bone Cyst - Nolan Maloney; Konstantinos Linos (SAGE Publishing, 2019)
Fibrous dysplasia is a benign, mass-forming disease of bone composed of abnormal fibrous and osseous elements that can be accompanied by endocrine dysfunction, skin pigmentation, and intramuscular myxomas. It is usually encountered as a solitary lesion in the tibia or femur but can develop in any bone and can be unifocal or multifocal. Difficulty arises when a solitary lesion is identified in an uncommon site or when there are prominent secondary changes, such as aneurysmal bone cyst (ABC). Molecular studies are available as an adjunct to histomorphology to aid distinction from other entities. GNAS mutations, present in greater than 70% of fibrous dysplasia cases, help in the distinction from primary ABC and low-grade osteosarcoma, which exhibit different molecular abnormalities. We report a case of monostotic fibrous dysplasia in a lumbar vertebral body with secondary change consisting of the solid variant of ABC.